1998
DOI: 10.1021/ma9716544
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Polymers by Noncatalytic Addition−Fragmentation Chain Transfer:  Modeling and Simulation of End-Group Functionality and Molecular Weight Distribution for High-Conversion Reactions in a Batch Process

Abstract: Kinetic models of free radically initiated polymerizations involving chain transfer by the noncatalytic addition−fragmentation mechanism have been simulated with the aim of finding the effect of conversion on the molecular weight, molecular weight distribution, and the efficiency with which specific end-group-functionalized polymers are produced. The specific situations explored are those where (i) the magnitude of the chain transfer constant is varied in processes where the rate of initiation is moderate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…1). Polydispersities were mostly in the expected range for nonreversible6 AFCT polymerization (1.5–2.0). Some low MW copolymers had slightly higher polydispersities, and a few copolymers had polydispersities of 1.4–1.2.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1). Polydispersities were mostly in the expected range for nonreversible6 AFCT polymerization (1.5–2.0). Some low MW copolymers had slightly higher polydispersities, and a few copolymers had polydispersities of 1.4–1.2.…”
Section: Resultsmentioning
confidence: 92%
“…The CTA 1 is an allylic sulfide that undergoes efficient chain transfer with growing polymer free radicals from many single monomer systems, followed by rapid fragmentation as shown: The fragmented t ‐butyl thiyl radical forms the end group to a new polymer molecule and leaves behind an olefinic polymer end group, which may be used in the production of grafted copolymers. With a moderate initiation rate and efficient chain transfer, kinetic modeling has shown that for end‐group functionalization (i.e., the production of polymer molecules with one olefinic end group and one t ‐butyl thiyl end group in this case), as much as 84% at an 80% conversion can be achieved in a system free of side reactions 6. In this work, we have investigated the efficiency of 1 as a CTA in the copolymer system, and we used NMR analysis to identify end groups and to estimate the efficiency of end‐group functionalization of the copolymers produced.…”
Section: Introductionmentioning
confidence: 99%